(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2024)
The intersection of fine arts and cinema has given rise to experimental films that transcend traditional narrative structures, positioning cinematic works as autonomous visual art expressions. This paper examines how filmmakers integrate principles of painting,